GEMINs: potential therapeutic targets for spinal muscular atrophy? - Borg, Rebecca; Cauchi, Ruben J. (Frontiers in Neuroscience, 2014)
The motor neuron degenerative disease spinal muscular atrophy (SMA) remains one of the most frequently inherited causes of infant mortality. Afflicted patients loose the survival motor neuron 1 (SMN1) gene but retain one or more copies of SMN2, a homologue that is incorrectly spliced. Primary treatment strategies for SMA aim at boosting SMN protein levels, which are insufficient in patients. SMN is known to partner with a set of diverse proteins collectively known as GEMINs to form a macromolecular complex. The SMN-GEMINs complex is indispensible for chaperoning the assembly of small nuclear ribonucleoproteins (snRNPs), which are key for pre-mRNA splicing. Pharmaceutics that alleviate the neuromuscular phenotype by restoring the fundamental function of SMN without augmenting its levels are also crucial in the development of an effective treatment. Their use as an adjunct therapy is predicted to enhance benefit to patients. Inspired by the surprising discovery revealing a premier role for GEMINs in snRNP biogenesis together with in vivo studies documenting their requirement for the correct function of the motor system, this review speculates on whether GEMINs constitute valid targets for SMA therapeutic development.